EFFECT OF SUGARS &LYSINE OF BROAD BEAN FLOUR ADDING TO WHEAT FLOUR (COMPOSITE ) ON BROWN INDEX & FERMENTATION PRESSURE GAS - Mazin M. Al- Zubaidy (Mesopotamia Journal of Agriculture)
The study was conducted to determine reducing & non reducing sugars and lysine content of three species ( Sham , ILB and Aquadulce ) of Broad bean seed flour ( Vicia faba ) which obtained from ICARDA Ninevah / Iraq and were compared with those of wheat flour. Different types of composite flour were prepared by partial substation of wheat flour with10, 20 and 30 % of Broad bean flour, also to study the effect of their content of reducing sugars and lysine on Brown index and Fermentation pressure gas. The content of wheat flour from non reducing and reducing sugars was 1.31 and 0.17% respectively, their content in sham broad bean flour was 4.13and 0.37% respectively, and for ILB specie was 4.21and 0.31% respectively , and for Aquadulce specie was 4.20and 0.39 % respectively, lysine content of wheat flour was 1.85mg /100gm and their content in sham , ILB and Aquadulce flour was402, 416 and 420 mg / 100 gm respectively. Result of study showed that the fermentation pressure gas values of composite dough increased with increasing substation ratio of all species of broad bean used in this study. Adding broad bean flour of three species to wheat flour caused increasing in brown index of composite flour comparing with wheat flour and caused color darkening of baked products from composite flour ( lab loaf ، cake and biscuit ).